Improving Students’ Reading Comprehension in Narrative Text through Thieves Strategy to the 10th Grade Students of MAN 1 Pangkalpinang - Indrawati, Indrawati; Widiana, Ade (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
The objectives of the research were; to describe the implementation of THIEVES strategy to the 10th grade students of MAN 1 Pangkalpinang; to figure out if there is any significant difference between the students who are taught by using THIEVES strategy and the students who are not taught by using non - THIEVES strategy to the 10th grade students of MAN 1 Pangkalpinang. In this research the researcher used quantitative approach with experimental research that was quasi-experimental design. The total samples was 78 students, consisted of X MIA 3 was 39 students as experimental group and X IIS 1 was 39 students as control group. The result of the test was analyzed by using SPSS 22.0 of Paired Sample t-test and Independent sample t-test. Based on the result of analysis there were two research findings. First, the implementation of THIEVES strategy usage could improve students’ reading comprehension in narrative text. It could be seen that the pre-test mean score in experimental group was 46.000 and control group was 45.179. Meanwhile, the post-test mean score in experimental group was 70.769 and control group was 68.461. Second, there was a significance difference between students who were taught by using THIEVES strategy and students who were not. It was known from the result of independent samples t-test. The t obtained was higher than t table (5.872 > 1.684) and the p output was lower than computation with level significant (0.000 < 0.05). It means that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. It could be concluded that THIEVES strategy was effective to improve students’ reading comprehension.